Unravelling Mortality in Enslavement. Patterns and Determinants of Mortality Among the Enslaved Population of Curaçao, 1839–1963 - Wieke Elien Metzlar; Nadeche Diepgrond (Historical Life Course Studies)
Examining demographic patterns of enslaved populations can shed light on living conditions of people living in slavery. During the 19th century, enslaved populations in Latin America and the Caribbean were characterized by an excess of deaths, indicating the harsh living conditions they were forced to live in. The island of Curaçao — at that time a Dutch colony — however, has formed an exception to this trend, as the enslaved population was characterized by natural increase. Today, newly crowdsourced data of the slave registers of Curaçao enables the examination of the entire enslaved population, which facilitates the study of (changes in) the demographic development on the island. This paper aims to gain insight into patterns of mortality between 1839 and 1863 in order to shed light on the determinants of the exceptional demographic development of the enslaved population of Curaçao. This research examines the mortality rates of the population and explores possible determinants — seasonality, sex and age — of this unique mortality pattern (n = 12,793). Previous research stressed the importance of the fertility pattern of Curaçao as the determinant in the natural increase of the population, however, the results showed that mortality might have played a more decisive role.  The relatively low mortality rates allowed fertility rates to exceed, and so, this positive difference between birth and death resulted in a unique pattern of natural increase of an enslaved population in the Caribbean.